(untitled) (Academicia Globe: Inderscience Research, 2023)
The service sector encompasses a broad range of industries that provide products and services to customers. From banking, hospitality, transportation, healthcare, and retailing, the service sector plays a key role in the global economy. One key factor that enables this sector to become successful is the ability to provide services to a diverse customer base. For this reason, the importance and prospects of learning foreign languages in the service sector cannot be overstated.